Fecal blood loss: A quantitative method of evaluating hemostasis in patients with thrombocytopenia. Issue 2 (9th November 2020) - Slichter, Sherrill J.; Gernsheimer, Terry; LeBlanc, Renee; Townsend‐McCall, Dee; Jones, Mary Kay; Cuaron, Linda; Bolgiano, Doug
Abstract: Background: The purpose of our studies was to determine if fecal blood loss can provide a quantitative measure of bleeding at platelet counts of 20 000/μL or less in patients with hypoproliferative thrombocytopenia and to document the effects of different prophylactic platelet transfusion triggers on fecal blood loss. Methods and Materials: Patients had an aliquot of their autologous red blood cells (RBCs) labeled with 51 Cr. Following reinjection of their radiolabeled RBCs, all feces and a daily blood sample were collected to determine fecal blood loss per day. Three different studies were performed in patients with thrombocytopenia: The first was in patients with thrombocytopenia with aplastic anemia who were not receiving platelet transfusions, and the other two trials involved thrombocytopenic patients with cancer who were receiving prophylactic platelet transfusions at platelet transfusion triggers of 5000/μL, 10 000/μL, or 20 000/μL. Results: In patients with thrombocytopenia not receiving platelet transfusions, fecal blood loss does not increase substantially until platelet counts are 5000/μL or less. When platelet transfusions are given prophylactically to patients with cancer with chemotherapy‐induced thrombocytopenia at platelet counts of 5000/μL or less, fecal blood loss and red cell transfusion requirements are the same as those for patients transfused prophylactically at higher transfusion triggers of 10 000 platelets/μL or 20 000 platelets/μL. However, the total number of platelet transfusions needed increases significantly, and the duration of the patient's thrombocytopenia tends to be longer at the higher platelet transfusion thresholds. Conclusion: A prophylactic platelet transfusion threshold of 5000/μL or greater is sufficient to maintain hemostasis in patients with thrombocytopenia.